Industrial Real Estate is a key Pillar of Algeria’s Sustainable Economic Development - Henni, Ameur; Habache, Imran (Journal of Legal Studies and Researches, 2023)
Any investment must have a specific headquarters in order to conduct various related transactions with this investment, not to mention that it reflects the element of stability and security, so it receives great attention in order to preserve and promote it, which is clearly evident through the huge and diverse legal arsenal that came to organize it since independence until today.